1998
DOI: 10.1007/pl00005223
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of pregnancy on the role of nitric oxide in gastric emptying and non-adrenergic non-cholinergic relaxation in the rat

Abstract: The influence of pregnancy on the role of nitric oxide (NO) in gastric emptying and in non-adrenergic non-cholinergic (NANC) relaxation was studied in rats. The gastric emptying of a non-nutrient liquid solution and of polysterene beads was studied in non-pregnant (NP), 6 to 7 days pregnant (P7) and 18 to 20 days pregnant (P20) rats. Longitudinal muscle strips of the gastric fundus and circular muscle strips of the pylorus were isolated from NP and P20 rats and NANC relaxations were induced by electrical field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Even if the influence of sex hormones and pregnancy on gastric motility and emptying is not definitively established [1,2,[36][37][38][39], the relaxin-induced increase in amplitude of the nitrergic fast relaxations may have some physiological implications. In fact, recent studies have shown that enhanced nitrergic relaxations can be observed in the stomach of pregnant animals and that estrogens could enhance gastric transit time by increasing the amplitude of the relaxant responses [19].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Even if the influence of sex hormones and pregnancy on gastric motility and emptying is not definitively established [1,2,[36][37][38][39], the relaxin-induced increase in amplitude of the nitrergic fast relaxations may have some physiological implications. In fact, recent studies have shown that enhanced nitrergic relaxations can be observed in the stomach of pregnant animals and that estrogens could enhance gastric transit time by increasing the amplitude of the relaxant responses [19].…”
Section: Discussionmentioning
confidence: 95%
“…The exact role of the nitrergic NANC innervation and of the relaxant responses in gastric transit time is far from being clarified [19,38,40,41]. Nevertheless, it is widely accepted that an altered NO production may lead to gastrointestinal dysmotilities [42].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists that sex hormones influence gastrointestinal motility (21,32,37,38,40) and may contribute to the increase of NOS expression and NO production occurring in pregnancy (55,61). The identification of specific relaxin-binding sites in the smooth muscle cells of the gastrointestinal tract of pregnant pigs (42) suggests that this hormone also influences gut func- tions, in keeping with early reports that a relaxin preparation extracted from the ovary reduced the strength and the frequency of contractions in the rat ileum (26) and that relaxin had disruptive effects on the migrating myoelectric complex in the rat small intestine (25).…”
Section: Discussionmentioning
confidence: 99%